Winter Weather and Work Hours: Heterogeneous Effects and Regional Adaptation - Bo Liu; Barry Hirsch (Institute of Labor Economics (IZA), 2020)
Winter weather affects hours worked. We examine how work hours reported in the monthly Current Population Survey (CPS) vary with respect to snowfall in 265 metropolitan areas over the years 2004-2014. The effects of snowfall on work hours vary across types of workers, occupation, industry, and region. Losses in work hours due to snow events are particularly large in the South and among construction workers. An average daily inch of snowfall during a reference week reduces work by about an hour. Few of the hours lost from large snowfalls are "made-up" in subsequent weeks. A "back-of-an-envelope" calculation suggests that in an average year, snow leads to a 0.15 percent loss in annual hours worked, a small but nontrivial impact.
Keywords: J22; O4; Q54; 330; work hours and snow; regional adaptation; heterogeneity by industry; occupation; work type